Combination of Music, Artificial Intelligence, and Brainwaves for the Promotion of Mental Well-Being - Georgios Karachalios; Evina Makaroni (Dialogues in Clinical Neuroscience & Mental Health)
The convergence of music, neuroscience, and artificial intelligence presents a highly innovative field of research and application, with significant potential for addressing various issues related to mental health and human well-being. Through the exploration of brain waves and the influence of music on brain activity, it becomes evident that this technological synthesis can lead to new and dynamic forms of intervention that are more effective and personalized than traditional methods. The preceding research highlighted the fundamental relationship between different brainwave frequencies (alpha, beta, theta, delta) and specific psychological states, such as relaxation, concentration, or deep sleep. Auditory stimulation technologies—particularly those using binaural beats and other sound patterns—have already proven effective in inducing these desirable states. However, the real revolution lies in the integration of this knowledge with modern techniques of machine learning and deep learning. Artificial intelligence can provide a framework for continuous and real-time adaptation of the musical experience based on everyone’s brain state. On a theoretical level, adapting music through machine learning opens new avenues for understanding the connection between human perception and psychological states. The algorithms used can offer valuable insights into how different auditory stimuli affect human psychology, creating a dynamic framework for study across both psychology and neuroscience. This data could then be utilized to develop personalized therapeutic interventions and ultimately contribute to improving the overall quality of life.